Best research practices in psychology illustrating epistemoligiccal and pragmatic considerations with the case of relationship science. - Finkel, Eli J.; Eastwick, Paul W.
In recent years, a robust movement has emerged within psychology to increase the evidentiary value of our science. This movement which has analogs throughout the empirical sciences is broad and diverse, but its primary emphasis has been on the reduction of statistical false positives the present article addresses epistemological and pragmatic issues that we, as a field, must consider as we seek to maximize the scientific value of this movement. Regarding epistemology, this article contrasts the false-positives-reduction (FPR) approach with an alternative, the error balance (EB) approach, which argues that any serious consideration of optimal scientific practice must contend simultaneously with both false-positive and false-negative errors. Regarding pragmatics, the movement has devoted to a great deal of attention to issues that frequently arise in laboratory experiments and one-short survey studies, but it has devoted less attention to issues that frequently arise in intensive and/or longitudinal studies. We illustrate these epistemological and pragmatic considerations with the case of relationship science, one of the many research domains that frequently employ intensive and/or longitudinal methods. Specifically, we examine 6 research prescriptions that can help to reduce false-positive rates: prerefistration, prepublication sharing of materials, postpublication sharing of data, close replication, avoiding piecemeal publication, and increasing sample size. For each, we offer concrete guidance not only regarding how research can implore their research practices and balance the risk of false-positive and false-negative errors, but also how the movement can capitalize upon insight from research practices within relationship science to make the movement stronger and more inclusive. - - (from the authors)